IFAS Community Development: The Continued Importance of Rural Development - Mark A. Brennan (EDIS)
This paper is part of a series of discussions on community development. This series includes specialized papers on leadership development, civic engagement, community action, and other topics important to the development of community. This document is FCS9242, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date May 2006.